Investigating Diagnostic and Treatment Barriers in Cancer Care: A Rural Perspective from Western Maharashtra, India - Akash Nagar; Kavita Vishwakarma; Gayatri R. Nair; Akhil R.; Divya Madamanchi (Indian Journal of Medical and Paediatric Oncology, 2025)
Introduction Noncommunicable diseases, particularly cancer, are increasingly burdening India's health care system. Despite the implementation of various national cancer control programs, notable barriers to timely diagnosis and treatment persist, especially in rural regions.